2005
DOI: 10.1002/hc.20090
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of tellurium tetraiodide with 2,3‐dihydro‐1,3‐diisopropyl‐4,5‐dimethylimidazol‐2‐ylidene

Abstract: 2,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
56
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(58 citation statements)
references
References 14 publications
1
56
0
1
Order By: Relevance
“…The released dihalogen often participates in undesirable side reactions, leading to difficulty in controlling the reaction outcome. [3,4] The X 2 can be sequestered by the addition of a third species (i.e., cyclohexene, SnCl 2 ), provided the additional reagent does not interfere with the targeted reactions. [5,6] Within our laboratory we have found that starting with a Ch II source appears to largely circumvent this problem.…”
Section: Introductionmentioning
confidence: 99%
“…The released dihalogen often participates in undesirable side reactions, leading to difficulty in controlling the reaction outcome. [3,4] The X 2 can be sequestered by the addition of a third species (i.e., cyclohexene, SnCl 2 ), provided the additional reagent does not interfere with the targeted reactions. [5,6] Within our laboratory we have found that starting with a Ch II source appears to largely circumvent this problem.…”
Section: Introductionmentioning
confidence: 99%
“…The Te-C distances in 10 (2.136(4), 2.138(3) Å) are consistent with single bonds as they display no shortening indicative of multiple bond character and are similar to other representative Te-C single bonds (≈ 2.10 Å). [10,19] This underscores the difference in structure from 12, in that 10 cannot be represented as an analogue of 12a, but is best drawn as a heavy element analogue of 12b ( Figure 5). …”
Section: Figure 1 Examples Of Main Group Centered Dicationsmentioning
confidence: 95%
“…Unfortunately, these compounds readily undergo redox reactions in the presence of strong Lewis bases, often to the elemental form, precluding access to the target compounds. [7][8][9][10] Nevertheless, success in generating highly charged (dicationic) S and Se species has been achieved by utilizing low valent dihalides as the chalcogen source (SCl2 or SeCl2). [11] For tellurium, no stable binary dihalide reagents are known, thus developing the corresponding chemistry for this heavier congener has remained elusive.…”
Section: Figure 1 Examples Of Main Group Centered Dicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[26,27] Coordination by Lewis bases allows for TeX 2 to be stabilized and stored. [28][29][30][31][32][33][34] Recently a few groups have used this strategy to deliver this otherwise unstable electrophilic Te II source. [35][36][37] Therefore, the proposed synthetic route to the tellurium NHC analogues is coordination by a DAB ligand to TeX 4 , followed by reduction and halide abstraction to give the dication.…”
Section: Introductionmentioning
confidence: 99%